Association between Silica Dust Exposure and Serum Transforming Growth Factor-β1 in Stone Quarry Workers - Wijaya, I Putu Eka Krisnha; Rai, Ida Bagus Ngurah; Andrika, I Putu (UI Scholars Hub, 2019)
Introduction. Silicosis is a disease that most often occurred as a result of silica dust exposure. Silica dust particles will stimulate alveolar macrophages to secrete proinflammatory mediators for fibroblast proliferation and collagen deposition. TGF-ß1 is one of the most extensively involved mediators in the development of fibrosis. To date, several studies have not shown consistent results regarding the association between silica dust exposure and TGF-β1. This study examined silica dust exposure and serum TGF-β1, which aims to determine the risk of silicosis in stone quarry workers. Methods. An analytic cross-sectional study was conducted at Company X, Karangasem in March 2016. The studied variables were silica dust exposure using nephelometer dust monitoring, serum TGF-β1 using ELISA method, nutritional status from weight scales, with age, smoking, and use of personal protective equipment (PPE) from an interview. Spearman correlation test is used to determine the correlation between silica dust exposure with serum TGF-β1. Multivariate linear regression analysis was used to asses the effect of silica dust exposure, age, nutritional status, cigarette smoking, and use of PPE with TGF-β1 serum. Results. There were 55 samples of stone quarry workers in this study. From the Spearman correlation test, there was a significant correlation between silica dust exposure with serum TGF-β1¬, (r) = 0.319, p = 0.018. In multivariate regression analyzes test, there were significant associations between silica dust exposure and nutritional status with serum TGF-β1, p = 0.042 and p = 0.012. Conclusions. There was an association between silica dust exposure and increasing serum TGF-β1 of stone quarry workers.